STRATEGI PEMBELAJARAN SENI TARI DI SMP NEGERI 35 PADANG - Ramadhani, Maziyah; Susmiarti, Susmiarti (SENDRATASIK UNP, 2019)
AbstractÂ The research aims to find and describe the strategies undertaken in the study of cultural arts, especially on the materials of dance art at SMP Negeri 35 Padang. This type of research is qualitative research using descriptive methods of analysis. The instrument in this study is self-researcher and assisted with supporting instruments such as stationery and cameras. Data collection types use primary data and secondary data. Data collection techniques are conducted by way of library studies, observation, interviews, documentation. Data analysis is done with the observation steps, interviews and teacher behaviour. The results showed that the learning process of dance art in SMP Negeri 35 Padang has not been carried out well and has not achieved the objective of learning to the maximum because the strategy used has not been fully implemented. This is because teachers lack the material and delivery of less interesting material that makes students bored and not focus on the learning. Choosing the right method is a plan for the purpose of learning to be accomplished well. Teachers are more likely to use lecture methods only. There are advantages for schools that have the completeness of facilities and infrastructure. First, completeness of facilities and means can foster the passion and motivation of teaching teachers. Secondly, the completeness of facilities and infrastructure can provide a variety of options for students to learn.Â Keywords: strategy, dance art Learning